Effect of Prehospital Crushed Prasugrel Tablets in Patients With ST-Segment–Elevation Myocardial Infarction Planned for Primary Percutaneous Coronary Intervention: The Randomized COMPARE CRUSH Trial. Issue 24 (15th December 2020) - Vlachojannis, Georgios J.; Wilschut, Jeroen M.; Vogel, Rosanne F.; Lemmert, Miguel E.; Delewi, Ronak; Diletti, Roberto; van der Waarden, Nancy W.P.L.; Nuis, Rutger-Jan; Paradies, Valeria; Alexopoulos, Dimitrios; Zijlstra, Felix; Montalescot, Gilles; et al.
Abstract : Background: Early treatment with a potent oral platelet P2Y12 inhibitor is recommended in patients presenting with ST-segment–elevation myocardial infarction scheduled to undergo primary percutaneous coronary intervention (pPCI). The impact on coronary reperfusion of crushed P2Y12 inhibitor tablets, which lead to more prompt and potent platelet inhibition, is unknown. Methods: We conducted a randomized controlled, multicenter trial in the Netherlands, enrolling patients with ST-segment–elevation myocardial infarction scheduled to undergo pPCI. Patients were randomly allocated to receive in the ambulance, before transfer, a 60-mg loading dose of prasugrel either as crushed or integral tablets. The independent primary end points were thrombolysis in myocardial infarction (TIMI) 3 flow in the infarct-related artery at initial coronary angiography, and complete (≥70%) ST-segment resolution 1 hour after pPCI. The safety end points were TIMI major and Bleeding Academic Research Consortium ≥3 bleedings. Secondary end points included platelet reactivity and ischemic outcomes. Results: A total of 727 patients were assigned to either crushed or integral tablets of prasugrel loading dose. The median time from study treatment to wire-crossing during pPCI was 57 (47–70) minutes. The primary end point TIMI 3 flow in the infarct-related artery before pPCI occurred in 31.0% in the crushed group versus 32.7% in the integral group (odds ratio, 0.92 [95% CI, 0.65–1.30], P =0.64). Complete ST-segment resolution 1 hour after pPCI was present in 59.9% in the crushed group versus 57.3% in the integral group (odds ratio, 1.11 [95% CI, 0.78–1.58], P =0.55). Platelet reactivity at the beginning of pPCI, measured as P2Y12 reactivity unit, differed significantly between groups (crushed, 192 [132–245] versus integral, 227 [184–254], P ⩽0.01). TIMI major and Bleeding Academic Research Consortium ≥3 bleeding occurred in 0% in the crushed group versus 0.8% in the integral group, and in 0.3% in the crushed group versus 1.1% in the integral group, respectively. There were no differences observed between groups regarding ischemic events at 30 days. Conclusions: Prehospital administration of crushed prasugrel tablets does not improve TIMI 3 flow in the infarct-related artery before pPCI or complete ST-segment resolution 1 h after pPCI in patients presenting with ST-segment–elevation myocardial infarction scheduled for pPCI. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03296540. Abstract : Supplemental Digital Content is available in the text.